Proceso de atención de enfermería en adolescente con diagnóstico de esquizofrenia. - Moreira Magarisca, Liliana Stefania (2023)
Schizophrenia is a serious mental disorder that affects thinking, feelings, and behavior. This results in significant deficits in relationship and self-control in people with this disease. Schizophrenia is a heterogeneous disease with rare genetic mutations. However, it is impossible to identify a single pattern of genetic alterations that cause this disorder. Genetic inheritance is highly associated with schizophrenia and has been shown to influence 65-81% of the development of symptoms of the disease. If both parents have the disorder, the probability increases to 50%. Cannabis users are six times more likely to develop schizophrenia than non-users, but other factors such as cocaine, alcohol and tobacco can also cause schizophrenia. The cause of schizophrenia is still not clear. Some theories about the cause of this disease include genetic, biological. The symptoms are not specific, but they vary a lot, being able to appear in other mental illnesses. Currently divided into positive and negative categories. A psychiatrist must examine the person and make a diagnosis based on interviews with the person and their family. According to the 11 functional patterns of MARJORY GORDON, it was possible to identify the patterns that in this model are the ones that best fit schizophrenic patients; With the help of the NANDA, NIC and NOC taxonomies, it was possible to identify a timely nursing diagnosis and thus create a care plan prioritizing the disease. Health personnel are also recommended to apply strategies to improve their crisis.